Analysis of cross-sectional area of digester on biogas production rate - Tira, H.S.; Padang, Y.A.; Sukrenewita, I.K. (Universitas Mataram, 2021)
Biogas has become one of the promising alternative fuels. This is triggered by relative ease of production while on the other hand the raw material is cheap and easy to be obtained. In order to get higher biogas production rate, a work has been done with digester cross-sectional area modification. Under the modification an improvement in biogas yield was obtained. The research also has opened up new outlook to set up a better digester design for maximum biogas production. The experimental results showed that a higher biogas volume yield was obtained in larger cross-sectional area compared to that of smaller one. Increasing the cross-sectional area twice will benefit at least three times in terms of biogas volume produced under similar raw material input volume. A wide-open cross-section surface is a major factor for good breeding of microbial to produce methane. Under the condition, microbes experience less pressure due to the evenly distributed volume of the substrate which resulted in a comfortable environment for bacteria.